2018
DOI: 10.14218/jcth.2017.00070
|View full text |Cite
|
Sign up to set email alerts
|

CA-125 Significance in Cirrhosis and Correlation with Disease Severity and Portal Hypertension: A Retrospective Study

Abstract: Background and Aims: To evaluate the prevalence and significance of elevated cancer antigen-125 (CA-125) levels in patients with cirrhosis being treated in a tertiary care liver center and its correlation with objective markers of disease severity.Methods: We retrospectively reviewed medical records of 172 adult patients with cirrhosis (due to any etiology) after obtaining CA-125 serum analysis. Demographics, etiology of cirrhosis, model of end-stage liver disease (MELD) score, Child’s Turcotte-Pugh classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…Also, serum CA19.9 and CA125levels were significantly higher in sever fibrotic patients than in mild fibrosis group. This is in accordance to several reports which illustrated an elevation of the tumor marker CA19.9 (Bertino et al, 2007, Bertino et al, 2013, Haque et al, 2015 and CA125 (Deschenes et al, 2001, Edula et al, 2018 in patients with liver cirrhosis. In addition, Singhal et al (2012) clarified that CA 19.9 and CA THE IMPACT OF CYCLOOXYGENASE-2 GENE ……..…”
Section: ‫ـــــــــــــــــــــــــــــــــــــــــــــــــــــــــــsupporting
confidence: 93%
“…Also, serum CA19.9 and CA125levels were significantly higher in sever fibrotic patients than in mild fibrosis group. This is in accordance to several reports which illustrated an elevation of the tumor marker CA19.9 (Bertino et al, 2007, Bertino et al, 2013, Haque et al, 2015 and CA125 (Deschenes et al, 2001, Edula et al, 2018 in patients with liver cirrhosis. In addition, Singhal et al (2012) clarified that CA 19.9 and CA THE IMPACT OF CYCLOOXYGENASE-2 GENE ……..…”
Section: ‫ـــــــــــــــــــــــــــــــــــــــــــــــــــــــــــsupporting
confidence: 93%
“…More than 25 years ago our group published a prospective and comprehensive study of 159 patients with liver diseases, including 85 cirrhotics with and without ascites 3. In this article, cited by Edula et al as their reference 14, we found the same results as Edula et al 1 reported for ascitic and non-ascitic patients 1. Moreover, our group published other articles focused exclusively on patients without ascites 9,10.…”
supporting
confidence: 76%
“…Moreover, our group published other articles focused exclusively on patients without ascites 9,10. Like Edula et al ,1 we found that elevations of CA-125 concentrations in patients without ascites were uncommon, but also that these elevations were related to the degree of liver dysfunction.…”
supporting
confidence: 71%
See 2 more Smart Citations